3D-Analysis of a non-planispiral ammonoid from the Hunsruck Slate: natural or pathological variation? - Stilkerich, Julia; de Baets, Kenneth; Smrecak, Trisha A. (PeerJ, 2017)
We herein examine the only known non-planispirally coiled early Devonian ammonoid, the holotype specimen of Ivoites opitzi, to investigate if the host was encrusted in vivo and if these sclerobionts were responsible for the trochospiral coiling observed in this unique specimen. To test if the presence of runner-like sclerobionts infested the historically collected specimen of Ivoites opitzi during its life, we used microCT to produce a three-dimensional model of the surface of the specimen. Our results indicate that sclerobionts grew across the outer rim (venter) on both sides of the ammonoid conch at exactly the location where the deviation from the planispiral was recognized, and where subsequent ammonoid growth would likely preclude encrustation. This indicates in vivo encrustation of the I. opitzi specimen, and represents the earliest documentation of the phenomenon. Further, this suggests that non-planispiral coiling in I. opitzi was likely pathologically induced and does not represent natural morphological variation in the species. Despite the observed anomalies in coiling, the specimen reached adulthood and retains important identifying morphological features, suggesting the ammonoid was minimally impacted by encrustation in life. As such, appointing a new type specimen-as suggested by some authors-for the species is not necessary. In addition, we identify the sclerobionts responsible for modifying the coiling of this specimen as hederelloids, a peculiar group of sclerobionts likely related to phoronids. Hederelloids in the Devonian are commonly found encrusting on fossils collected in moderately deep environments within the photic zone and are rarely documented in dysphotic and aphotic samples. This indicates that when the ammonoid was encrusted it lived within the euphotic zone and supports the latest interpretations of the Hunsrck Slate depositional environment in the Bundenbach-Gemunden area.
Keywords: Epicole; Pathology; Computed tomography; Hederelloidea; Ammonoidea; Epizoa; Heteromorph; Three-dimensional reconstruction; CT scan; Intraspecific variation